Ionic liquids vs. ethanol as extraction media of algicidal compounds from mango processing waste - Segatto, Mateus L.; Schnarr, Lena; Olsson, Oliver; Kümmerer, Klaus; Zuin, Vania G. (Frontiers in Chemistry, 2022)
The race for environmentally-safe pesticides and biocides has been showing solutions ranging from pest-pathologic microorganisms to safer botanical extracts that can be incorporated in several formulations. Often linked to high biological activities, fruit residues can be recovered from food processing factories to obtain complex extracts enriched with several bioactive chemicals. Mango (Mangifera indica) fruits are processed into food products in high volumes across the globe and generate a consistent residue that contains, among others, the xanthonoid mangiferin and the flavonoid hyperoside. Both compounds have been linked to several pharmacological and pesticidal activities, although not yet studied for algicidal applications, a current concern specially for antifouling and harmful algae blooms control products. The challenge lies, however, not only on the degree of activity of the natural compounds, but also on the processes necessary to separate, isolate and formulate the bioactive compounds in order to obtain an effective final product. The solvent choice plays an important part regarding the selectivity of the separation and isolation of the main bioactive compounds from the solid waste matrix. Ethanolic mixtures in water have been consolidated recently as a promising extraction medium for flavonoids and xanthonoids, although hindered by solubility limitations. In this paper, aqueous solutions of ionic liquids (ILs) were tested, screened and optimized using Box-Behnken design and Response Surface Methodology to obtain mangiferin and hyperoside-enriched extracts. Results showed a greater concentration of mangiferin and hyperoside with 1-octyl-3-methylimidazolium chloride ([C8MIm] Cl), when compared to choline acetate and ethanolic extracts using optimized parameters. In terms of sufficiency, solvent selection between ILs and ethanolic extraction media was discussed considering economic and environmental factors. Ethanol/water mango waste extracts were then studied for their activity against Raphidocelis subcapitata microalgae, which showed a higher growth inhibition in comparison to standard solutions of mangiferin and hyperoside, either individually and in a 1:1 mixture. A EC50 value was found in relative low concentrations of mangiferin and hyperoside (0.015 mg L-1) detected in the extract, showcasing a promising approach to the direct use of residuary plant extracts in biocidal formulations.